Examining the town planning scheme of India and lessons from land readjustment in Japan - Vibhu Jain (Asian Development Bank Institute (ADBI), 2019)
Land is a scarce resource; hence, efficient land management techniques are critical for its procurement and development. The land readjustment (LR) mechanism is one such land assembly tool, which many countries, including Japan, have adopted, and is known as the Town Planning Scheme (TP Scheme) in India. This is the concept of replotting or reshaping a parcel of land to develop it with amenities and services, such as roads, parks, social infrastructure, and utilities. In India, the TP Scheme was institutionalized more than 100 years ago, but legal, institutional, and financial challenges have caused scant implementation, with successful cases are mostly concentrated in the state of Gujarat. Japan has been far more successful in implementing the scheme, developing one-third of the urbanized land through the LR mechanism (Matsui 2018). The experience of continuously implementing many LR projects in Japan has made the Japanese LR system mature in terms of the approval process, land replotting techniques, and financing, contributing to quicker and smoother implementation. The way forward for India could be to scale up the use of the TP Scheme by gathering skilled resources and drafting a competent financial framework for executing projects, learning from success stories, and self-evolving through continuous implementation.
Keywords: R31; R4; R23; 330; land pooling; India; land readjustment; Japan; urbanization